Adaptación a la variabilidad climática entre los caficultores de las cuencas de los ríos Porce y Chinchiná, Colombia (2014)
ABSTRACT: This article seeks to explain the practices used by small farmers to cope with climate variability and extreme weather events in the basins of the Chinchiná and Porce rivers located on the central Andes in Colombia. The information wasglacie collected through interviews, observations on farms and workshops with farmers. Additionally historical averages on temperature, precipitation and sunshine were compared with those values recorded in 2010 during the transition between El Niño an La Niña events. During the first quarter of 2010 the average temperature in Chinchiná increased by 1.4 C° and the solar brightness by 14%, while the precipitation experienced a 46% reduction. In contrast, during the second half of the year there was a decrease of 0.8 C° in temperature, a 31% reduction in solar brightness and an increase in precipitation of 62%. The coffee production in the years 2011 and 2012 was the lowest in the country in the last 35 years despite the cultivated area increased.